1,3-Bis[(4-nitrobenzylidene)aminooxy]propane - Dong, Wen-Kui; Sun, Yin-Xia; Tong, Jun-Feng; Zhao, Hai-Hong; Wang, Li (Acta crystallographica. Section E, Structure reports online, 2009)
The complete molecule of title compound, C(17)H(16)N(4)O(6), is generated by a crystallographic twofold axis. Within the mol-ecule, the two benzene units are approximately perpen-dicular, making a dihedral angle of 85.91 (4)°. In the crystal, mol-ecules are linked into a three-dimensional network by C-H⋯O hydrogen bonds and short O⋯O and N⋯O inter-actions, with distances of 2.998 (2) and 2.968 (3) Å, respectively.